2004
DOI: 10.1007/s00198-003-1544-7
|View full text |Cite
|
Sign up to set email alerts
|

Undertreatment with anti-osteoporotic drugs after hospitalization for fracture

Abstract: This study assessed the proportion of patients treated with anti-osteoporotic drugs during the 1-year period after hospitalization for a fracture, and the influence of a guideline in the period 1998-2000 on the likelihood of receiving treatment for osteoporosis after a fracture. Patients were assessed retrospectively for anti-osteoporotic drug use during a 1-year period following hospitalization for non-traumatic fracture. The PHARMO system, a population-based database ( n=865,000) containing drug and hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(69 citation statements)
references
References 14 publications
3
62
0
4
Order By: Relevance
“…Use of osteoporosis medications prior to fracture was not included as a predictor in the current study as not all residents included had had a fracture. An increased likelihood of osteoporosis management among females has been reported previously among community-living individuals with fragility fractures [14,[38][39][40][41][42][43], among home care recipients [15] and among LTC residents in the USA [20,21]. Although gender was not a predictor of treatment in the current study, previous studies reporting that osteoporosis tends to be overlooked in males suggest the need to initiate osteoporosis investigation in males as well as females to ensure that at-risk males receive adequate management.…”
Section: Discussionmentioning
confidence: 40%
“…Use of osteoporosis medications prior to fracture was not included as a predictor in the current study as not all residents included had had a fracture. An increased likelihood of osteoporosis management among females has been reported previously among community-living individuals with fragility fractures [14,[38][39][40][41][42][43], among home care recipients [15] and among LTC residents in the USA [20,21]. Although gender was not a predictor of treatment in the current study, previous studies reporting that osteoporosis tends to be overlooked in males suggest the need to initiate osteoporosis investigation in males as well as females to ensure that at-risk males receive adequate management.…”
Section: Discussionmentioning
confidence: 40%
“…In particular, the percentage of hip fracture patients who received prescription for anti-osteoporosis drugs was 19% in the study by Gardner et al [16] and 15% in the study by Panneman et al [17]. A large study carried out in Belgian patients who had sustained hip fracture reported that only 6% received treatment [8].…”
Section: Discussionmentioning
confidence: 95%
“…1,2 Even after a fracture, fewer than 25% of patients receive pharmacologic treatment for osteoporosis. [3][4][5] After the discovery that sclerostin deficiency causes rare genetic conditions that are characterized by high bone mass and resistance to fracture, 6,7 sclerostin became a therapeutic target for the treatment of osteoporosis. Sclerostin, a negative regulator of bone formation that is secreted by osteocytes, 8 inhibits Wnt signaling, down-regulating this stimulus for osteoblast development and function.…”
mentioning
confidence: 99%